Community Participation in the Development of "Kapalo Banda" Tirta Tourism Nagari Taram, Lima Puluh Kota, Sumatra Barat - Fauzan, Muhammad; Hendri, Ridar; Zulkarnain, Zulkarnain (Jurnal Perikanan dan Kelautan, 2025)
Community participation is an opportunity for local residents to actively contribute to the management of tirta tourism. Kapalo Banda Tirta Tourism is managed by the community with involvement as tourism managers and business owners around the Kapalo Banda irrigation waters and the forest in Nagari Taram. This research aims to describe the stages of participation, analyze the degree of participation and identify the supporting and inhibiting factors affecting community participation in the development of Kapalo Banda Tirta Tourism. The method used is descriptive research with a qualitative approach. In this research, the informants were selected purposively including representative from the Nagari Taram Government, tourism manager and business owner. The data analysis method used is Miles and Hubberman’s analysis, which starts with data reduction, presentation and drawing conclusions. The results of the research are (1) the stages of community participation in Nagari Taram is involved in all stages, including the decision making stage, the implementation stage, the benefit taking stage and the evaluation stage. (2) The degree of community participation in Nagari Taram is categorized as degree of tokenism. (3) The supporting factors for community participation in Nagari Taram are motivation, funds and personal assets, opportunities, training and socialization while inhibiting factors include weather and natural disasters, regulations for becoming a tourism manager, other jobs and the influence of negative activities.